Experiences of internationally qualified nurses in adapting to the Australian healthcare system: A scoping review - Ferry Efendi; Rifky Octavia Pradipta; Makhfudli Makhfudli; Lisa McKenna; Grace Solely Houghty; Fitri Kurnia Rahayu; Fildzah Cindra Yunita (International Journal of Nursing Studies Advances)
Background: Internationally qualified nurses commonly face challenges related to language barriers, cultural adaptation, and recognition of prior professional skills. Purpose: We aimed to map and synthesise the literature about the experiences of Internationally qualified nurses transitioning into the Australian healthcare system and to identify key challenges and gaps in supporting their integration and professional development. Methods: A scoping review was conducted using a comprehensive search across five databases (Ovid MEDLINE, EBSCO CINAHL, Embase, Scopus, and Web of Science Core Collections), covering the literature from January 2014 to August 2024. Two researchers screened, selected relevant, and performed data charting, independently. The Patterns, Advances, Gaps, Evidence for practice, and Research recommendations framework was implemented to collate, summarise, and report the finding, while the review’s report was formulated per the PRISMA-ScR guideline. Results: Fifteen studies were deemed suitable and synthesised from which we revealed that internationally qualified nurses underwent complex and multifaceted transitions. They faced language barriers, challenges in cultural adaptation, inadequate recognition of professional skills, and inconsistent access to support resources. Despite these hurdles, they demonstrated remarkable resilience. Language and communication challenges, particularly among nurses from non-English-speaking backgrounds, were common and impacted job satisfaction and integration. Meanwhile, discrimination and cultural biases were also reported, which contributed to feelings of isolation. Finally, orientation programs and mentorship proved beneficial support; however, inconsistencies in support availability remains a key gap. Conclusions: Internationally qualified nurses’ experiences reflected the need for tailored language support, standardised skill recognition, anti-discrimination policies, and consistent orientation resources to enhance integration. Addressing these gaps could not only improve internationally qualified nurses’ job satisfaction, retention, and overall professional development within the Australian healthcare system but also contribute to a more diverse and inclusive healthcare workforce.